2013
DOI: 10.1002/ana.23835
|View full text |Cite
|
Sign up to set email alerts
|

N400 predicts recovery from disorders of consciousness

Abstract: Results specify cognitive capabilities in disorders of consciousness, and determine their prognostic value. Specifically the N400 ERP is suggested as an important tool to assess information-processing capacities that can predict the likelihood of recovery of patients in UWS or MCS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
102
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(115 citation statements)
references
References 33 publications
3
102
1
3
Order By: Relevance
“…Indeed, whereas a clear central negativity was present in DOC patients, both the ROI and the regression analyses showed only marginal values of similarity with the canonical N400. Concerning the earlier latency of patients' N400, we note that across the 6 previous studies conducted in DOC patients one found a discretely delayed (o20 ms) latency of N400 for incongruent trials (Balconi et al, 2013), whereas no specific information was reported in the other 5 articles (Kotchoubey, 2005;Rämä et al, 2010;Schoenle and Witzke, 2004;Steppacher et al, 2013). Larger series of patients with homogenous aetiologies would be necessary to establish reliable landmarks on this issue, as it is plausible that different aetiologies should be associated to different patterns of impairments of the brain's semantic networks.…”
Section: Verbal Semantic Processing In Non-communicating Patientsmentioning
confidence: 65%
See 1 more Smart Citation
“…Indeed, whereas a clear central negativity was present in DOC patients, both the ROI and the regression analyses showed only marginal values of similarity with the canonical N400. Concerning the earlier latency of patients' N400, we note that across the 6 previous studies conducted in DOC patients one found a discretely delayed (o20 ms) latency of N400 for incongruent trials (Balconi et al, 2013), whereas no specific information was reported in the other 5 articles (Kotchoubey, 2005;Rämä et al, 2010;Schoenle and Witzke, 2004;Steppacher et al, 2013). Larger series of patients with homogenous aetiologies would be necessary to establish reliable landmarks on this issue, as it is plausible that different aetiologies should be associated to different patterns of impairments of the brain's semantic networks.…”
Section: Verbal Semantic Processing In Non-communicating Patientsmentioning
confidence: 65%
“…Note that 4/6 patients with temporal lesions had a right temporal lesion. (Steppacher et al, 2013) recently reported an ERP study of semantic congruity conducted in 92 patients (53 VS and 39 MCS patients) with an additional measure of clinical outcome between 2 and 14 years after discharge from rehabilitation. They found signs of semantic processing in 32% of VS patients, and most importantly they reported a clear association between such ERP response and prognosis outcome, both in MCS and in VS patients.…”
Section: Verbal Semantic Processing In Non-communicating Patientsmentioning
confidence: 99%
“…Some previous research focalized on semantic processing by using classical linguistic task (Rämä et al 2010;Schoenle and Witzke 2004;Vanhaudenhuyse et al 2008). Preserved abilities were found in DOC in response to linguistic stimuli (Steppacher et al 2013). Functional skills to process semantic meaning were observed in some conditions, that is in MCS and sometimes in single-case reports of VS (Balconi et al 2013;Schoenle and Witzke 2004).…”
Section: Introductionmentioning
confidence: 97%
“…pitch discrimination, or recognition of nonsensical sentence endings (c.f. Harrison and Connolly, 2013;Monti, 2012;Steppacher et al, 2013). Unfortunately, these studies cannot answer the question of whether these patterns of activation reflect conscious awareness.…”
Section: Introductionmentioning
confidence: 98%